Photodynamic inactivation of microorganisms which cause pulmonary diseases with infrared light: An in vitro study - Leite, Ilaiáli S.; Geralde, Mariana C.; Salina, Ana C. [UNESP]; Medeiros, Alexandra I. [UNESP]; Kurachi, Cristina; Bagnato, Vanderlei S.; Inada, Natalia M. (SPIE, the international society for optics and photonics, 2014)
Lower respiratory infections are among the leading causes of death worldwide. In this study, it was evaluated the interaction of indocyanine green, a photosensitizer activated by infrared light, with alveolar macrophages and the effectiveness of the photodynamic therapy using this compound against Streptococcus pneumoniae. Initial experiments analyzed indocyanine green toxicity to alveolar macrophages in the dark with different drug concentrations and incubation times, and macrophage viability was obtained with the MTT method. The average of the results showed viability values below 90% for the two highest concentrations. Experiments with Streptococcus pneumoniae showed photodynamic inactivation with 10 μM indocyanine green solution. Further experiments with the bacteria in co-culture with AM will be conducted verifying the photodynamic inactivation effectiveness of the tested drug concentrations and incubation periods using infrared light. © 2014 SPIE.
Keywords: Alveolar macrophages; Infrared light; Photodynamic inactivation; Pulmonary diseases